Sosialisasi Pencegahan dan Penanganan Kekerasan Seksual di Perguruan Tinggi Melalui Pameran Karya Seni - Yohanes Jhony Kurniawan; Heppy Julianto; Antonia J. Laratmase (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This Community Service research This PKM (Community Service) activity aims to; Increased understanding of scholarship recipient students, scholarship recipient alumni, STMA Trisakti leaders, academic assistant lecturers for scholarship recipient students, alumni, and the surrounding community regarding activities to prevent and handle sexual violence in higher education through art exhibitions, and so it is hoped that this will increase the desire of students and alumni. , leaders of STMA Trisakti, academic assistant lecturers for scholarship recipient students and the surrounding community in activities to prevent and handle sexual violence. Using the Art Exhibition method. Participants who attended this PKM were 100 who came from scholarship recipients, both KIP, YBT, internship scholarships from STMA Trisakti, and in general from Trisakti Foundation Education units, such as the Trisakti Logistics Transportation Institute, STMK Trisakti, TSM Trisakti, IPT Trisakti, and Universities Trisakti.